Retrospective analysis of the results of surgical treatment of patients with primary and postoperative ventral herniations under the conditions of morbid obesity - Piatnochka, V. I.; Levchuk, R. D.; Dovha, I. I. (Journal of Education, Health and Sport, 2020)
48–78 % of patients admitted to surgical hospitals with ventral hernias are obese, which has a significant impact on the course of the disease and the postoperative period, and little is reported in the literature. Obesity, on the one hand, contributes to the formation of hernia, on the other – progresses with its appearance. Despite the large number of surgical procedures to correct the abdominal wall, the results of surgical treatment of primary and postoperative ventral hernias, especially in morbid obesity are unsatisfactory, due to errors in choosing the optimal method of surgery indicated by the high number of complications and high recurrence. Recurrences after surgical treatment of primary and postoperative ventral hernias occur in 10–60 % of cases, which indicates that the problem of surgical restoration of the abdominal wall is still far from being solved. Objective. Conduct a retrospective analysis of the results of surgical treatment of patients with ventral and postoperative ventral hernia to determine the main risk factors for complications in patients with morbid obesity. Materials and methods. The results of surgical treatment of 183 patients operated on for primary and postoperative ventral hernia with concomitant morbid obesity in 2015–2020 were analyzed. Exclusion criteria were constricted hernias of the anterior abdominal wall, comorbidities in the stage of decompensation or exacerbation. 141 women (76.84 %) and 42 men (23.16 %) underwent surgery. The age of patients ranged from 18 to 84 years (mean age – 53.4 ± 5.6 years). The duration of herniation ranged from 2 to 34 years. 45 (24.7 %) underwent surgery for primary ventral hernias. The remaining 138 (75.3 %) patients were operated on with postoperative ventral hernias. Results. Among the examined 183 patients with degree I of obesity there were 76 (41.42 %) patients, with degree II – 58 (31.48 %), and degree III – 49 (27.1 %) examined. In obese patients of degree II heart failure class I was confirmed in 17 (22.37 %), class II in 19 (32.73 %) and class III in 31 (63.27 %) surgically operated. Among patients with degree III of obesity cardiac class II was detected in 3 (5.17 %) and class III in 4 (8.16 %) surgically operated. With respiratory failure (RF) degree I 102 (55.74 %) patients underwent surgery, with RF degree II – 67 (36.61 %) and RF degree III – in 14 (7.65 %), respectively. Varicose veins of the lower extremities were affected 68 (37.18 %) patients. Diabetes was diagnosed in 21 (11.48 %), including 19 (10.38 %) patients with type II diabetes. Undifferentiated connective tissue dysplasia was diagnosed in 36 (19.46 %) patients. Own tissue hernioplasty was performed in 35 (19.13 %) patients. Prosthetic plasty was performed in most of the surgically operated 148 (80.86%), among them onlay in 25 (13.76 %), sublay in 79 (43.17 %), inlay in 26 (14.73 %), laparoscopic hernioplasty in 13 (6.72 %) respectively. Separation hernioplasty (components separation technique) was performed only in 5 (2.91 %) patients. In some patients, as a simultaneous stage of surgical intervention, hernioplasty was performed in combination with dermatolipectomy and liposuction. A total of 46 (25.14 %) were performed. Dermatolipectomies were performed by Kuster, Jolly, Thorek and Castansres-Goethel. Pulmonary artery thromboembolism (PE) was diagnosed in 2 (1.09 %) surgically operated: 1 (1.31 %) patient with degree I of obesity and 1 (1.72%) with degree II respectively. Abdominal compartment syndrome (ACS) was diagnosed in 4 (2.19 %) surgically operated: among them with obesity degree II – in 2 (3.45 %) patients and degree III – in 2 (4.08 %) patients. Significantly higher frequency of wound complications was observed in patients with obesity degree II – 15 (26.17 %) and degree III – 16 (31.41 %). Hernia recurrence occurred in 10 (12.58 %) surgically operated with obesity degree I, in 6 (9.33 %) with degree II, and in 6 (11.82 %) with degree III. Conclusions. Performance of laparoscopic and non-tension implantation methods of hernioplasty should be a priority, especially in groups of patients with pre-existing morbid obesity degree II–III. In obese patients with degree III there is a significantly higher incidence of abdominal compartment syndrome, and the simultaneous dermatolipectomy or liposuction significantly reduces the incidence of local complications and recurrences.